Cancer and its impact on work among the self‐employed: A need to bridge the knowledge gap. (8th August 2017) - Sharp, L.; Torp, S.; Van Hoof, E.; de Boer, A.G.E.M.
Abstract : Self‐employment—the so‐called flexible layer of the economy—has gained importance following the 2007–2008 global economic and financial crisis. In Europe, the self‐employed now comprise on average 15% of workers [Eurostat, Labour market and Labour force survey (LFS) statistics, 2016]. Around one‐third of self‐employed people also provide jobs for others [European Commission, Fact Sheet. 2015 Employment and Social Developments in Europe Review: frequently asked questions, 2016]. Moreover, this group of workers adapts quickly to changing circumstances. In the UK, for instance, recent growth in self‐employment is considered to have made an important contribution to labour market recovery [Hatfield, Self‐employment in Europe. London, Institute of Public Policy Research, 2015]. Across the European Union self‐employment is viewed as a key enabler of sustainable economic growth and, reflecting this, the Europe 2020 strategy encourages member states both to promote self‐employment and to remove measures that discourage it [Library of the European Parliament, Self‐employment and social security. Effects on innovation and economic growth, 2013].